2013
DOI: 10.1097/ico.0b013e3182a73802
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Visual Improvement With Prosthetic Replacement of the Ocular Surface Ecosystem Scleral Lenses for Irregular Corneas

Abstract: PROSE scleral lenses offer improvements in the VA and function, and they could be an option for patients with irregular corneas who have failed conventional treatments before considering additional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 13 publications
4
30
0
3
Order By: Relevance
“…20 As the severity of KC increases, CL fitting becomes more complex, and special designs to match the altered corneal shape may be required. In case of corneal GP lens failure due to disease severity or corneal GP lens intolerance, other options such as piggyback lenses (corneal GP lens fitted over a soft lens), 21 hybrid lenses (lens with a central GP portion and a soft skirt in the periphery), 22-25 scleral lenses, [26][27][28] or miniscleral lenses [29][30][31] are available. Popularity of scleral lenses for the correction of irregular corneas has increased in the recent years with the advent of better materials and designs.…”
Section: Contact Lensesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 As the severity of KC increases, CL fitting becomes more complex, and special designs to match the altered corneal shape may be required. In case of corneal GP lens failure due to disease severity or corneal GP lens intolerance, other options such as piggyback lenses (corneal GP lens fitted over a soft lens), 21 hybrid lenses (lens with a central GP portion and a soft skirt in the periphery), 22-25 scleral lenses, [26][27][28] or miniscleral lenses [29][30][31] are available. Popularity of scleral lenses for the correction of irregular corneas has increased in the recent years with the advent of better materials and designs.…”
Section: Contact Lensesmentioning
confidence: 99%
“…43 Piggyback lenses, hybrid lenses, scleral lenses, and mini scleral lenses have a role when corneal GP lenses have failed. [21][22][23][24][25][26][27][28][29][30][31]38,47 Piggyback lenses provided better vision, comfort, and corneal health. 21 In corneal GP lens-intolerant KC eyes, piggyback lenses worn for an average period of 6 months showed improvement in the tolerance level of corneal GP lenses.…”
Section: Contact Lensesmentioning
confidence: 99%
“…The PROSE is a non-fenestrated scleral CL that is filled with fluid prior to insertion in the eye. Treatment has a high success rate when measured by the ability to achieve satisfactory fit and impact on VA 31 34. PROSE treatment can be an alternative to PKP for patients with corneal ectasia who are CL intolerant 34.…”
Section: Managementmentioning
confidence: 99%
“…63,67,79,80,87,91,93,99,100,118,126 Other studies reported the number of patients who experienced an improvement of at least two lines of Snellen acuity. Improvements in visual acuity were reported in patients wearing scleral lenses for all indications.…”
Section: Case Reports/retrospective Case Seriesmentioning
confidence: 99%
“…Cotter and Rosenthal 69 Rosenthal et al 70 Rosenthal and Cotter 71 Rosenthal and Croteau 72 Jacobs and Rosenthal 73 Gungor et al 74 Lin et al 75 Lim et al 76 Grover et al 77 Gumus et al 78 Rathi et al 79 Baran et al 80 Cressey et al 81 Kalwerisky et al 82 Rathi et al 83,84 Dimit et al 85 Gire et al 86 Lee et al 87 Lim et al 88 Ling et al 89 Samimi et al 90 Arumugan et al 91 Ciralsky et al 92 Heur et al 93 Mahadevan et al 94 Rose K (Blanchard Contact Lens, Manchester, NH)…”
Section: Case Reports/retrospective Case Seriesmentioning
confidence: 99%